Auxin metabolism rates and implications for plant development - Kramer, Eric M.; Ackelsberg, Ethan M. (Frontiers in Plant Science, 2015)
Studies of auxin metabolism rarely express their results as a metabolic rate, although the data obtained would often permit such a calculation to be made. We analyze data from 31 previously published papers to quantify the rates of auxin biosynthesis, conjugation, conjugate hydrolysis, and catabolism in seed plants. Most metabolic pathways have rates in the range 10 nM/h to 1 μM/h, with the exception of auxin conjugation, which has rates as high as ~100 μM/h. The highest rates of auxin conjugation suggests that auxin metabolic sinks may be very small, perhaps as small as a single cell. By contrast, the relatively low rate of auxin biosynthesis requires plants to conserve and recycle auxin during long-distance transport. The consequences for plant development are discussed.